Students' perspective on offline and online learning in the Pencak Silat course - Novrityan Bayu Putra Putra; Siti Nurrochmah (Journal of Science and Education)
This study aims to examine the perspectives of students from the 2019 Health Physical Education and Recreation (PJKR) Program Study of the Faculty of Sport Science in State University of Malang regarding lectures using offline and online systems in the motion theory course and the martial arts practice course. The study used a quantitative descriptive survey design. The population of this study amounted to 227 students of the year 2019 PJKR Study Program. The sample of this study was 94 students and the analysis technique used was quantitative descriptive statistics. The results showed that student responses in offline lectures for theory courses were mostly positive as much as 94%, 79% positively agree with offline lectures for practical subjects, 70% respondents agree with online lectures for theory courses, and 89% students positively responded on online lectures for practical courses. Based on the research results obtained, it can be concluded that the response of the class of 2019 students to offline and online system lectures in theory and practice courses can be said to have been good and effective because they are in accordance with good learning principles.